Utilization and Predictors of Maternal Health Care Services among Women of Reproductive Age in Hawassa University Health and Demographic Surveillance System Site, South Ethiopia: A Cross-Sectional Study - Elsabet Shudura; Amanuel Yoseph; Alemu Tamiso (Advances in Public Health)
Background. Regular utilization of maternal health care services decreases maternal morbidity and mortality. However, major predictors that influence the utilization of the existing maternal health care services are complex and differ from place to place. Therefore, assessing these predictors assists health planners to prioritize promotion strategies and is a fundamental step for intervention. This study assessed the utilization and predictors of maternal health care services among women of the reproductive age in Hawassa Health and Demographic Surveillance System site, South Ethiopia, 2019. Methods. A community-based cross-sectional study was conducted among 682 women of the reproductive age from January to February, in 2019. A two-stage stratified sampling method was utilized. Data were collected using a structured, face-to-face interviewer-administered questionnaire. The data were entered using Epi Data 3.1 and analyzed using SPSS version 20. The variables were entered into the multivariable model using the backward stepwise regression approach. Multivariable logistic regression analysis was used to identify factors associated with utilization of the maternal health care. Adjusted odds ratios (AORs) with 95% confidence interval (CI) were computed to assess the presence and strength of associations. Result. The overall utilization of ANC, institutional delivery, and PNC was 69.1, 52.1, and 32.7%, respectively. The odds of utilizing ANC were 4.72 times higher for women who have a formal education (AOR: 4.72, 95% CI = 2.82–7.90) as compared to those who have no formal education. The odds of utilizing institutional delivery were 5.96 times higher for women who had ANC follow-up (AOR: 5.96; 95% CI = 3.88–9.18) as compared to those who had no ANC follow-up. Presence of information about the PNC (AOR: 3.66; 95% CI = 2.18–6.14) and autonomy of a woman to make decision on health issues (AOR: 6.13, 95% CI = 3.86–9.73) were positively associated with utilization of PNC. Conclusion. The utilization of maternal health care services is far below the national target in the study area. Maternal and paternal education status, autonomy of the woman to make decision on the health issues, wealth status, and having a plan on the current pregnancy were major predictors of the maternal health care service utilization. Providing information and training about the model household to the women about maternal health care service utilization using various methods of health education should be considered.